Diffusion of interstitial elements in Ti alloys used as biomaterials - Grandini, Carlos Roberto [UNESP]; De Almeida, Luciano Henrique [UNESP]; Nogueira, Renata Abdallah [UNESP]; Niemeyer, Terlize Cristina [UNESP] (My University, 2008)
Titanium alloys are excellent implant materials for orthopedic applications due to their desirable properties, such as good corrosion resistance, low elasticity modulus, and excellent biocompatibility. The presence of interstitial elements (such as oxygen and nitrogen) causes strong changes in the material's mechanical properties, mainly in its elastic properties. Study of the interaction among interstitial elements present in metals began with Snoek's postulate, that a stress-induced ordering of interstitials gives rise to a peak in the mechanical relaxation (internal friction) spectra. In the mechanical relaxation spectra, each species of interstitial solute atom gives rise to a distinct Snoek's peak, whose temperature and position depend on the measurement frequency. This effect is very interesting because its peculiar parameters are directly related to the diffusion coefficient (D) for the interstitial solute. This paper presents a study of diffusion of heavy interstitial elements in Ti-35Nb-7Zr-5Ta alloys using mechanical spectroscopy. Pre-exponential factors and activation energies are calculated for oxygen and nitrogen in theses alloys.
Keywords: Biomaterials; Diffusion; Interstitials; Mechanical spectroscopy